Bowel preparation for colonoscopy: comparison of mannitol and sodium phosphate. Results of a prospective randomized study - Habr-Gama, Angelita; Bringel, Robert William de Azevedo; Nahas, Sergio Carlos; Araújo, Sergio Eduardo de Alonso; Souza Junior, Afonso Henrique de; Calache, João Elias; Alves, Paulo Arruda (Revista do Hospital das Clínicas, 1999)
METHOD: Eighty patients were prospectively randomized for precolonoscopic cleansing either with 750 ml of 10% mannitol (Group M) or 180 ml of a sodium phosphate preparation (Group NaP). Laboratory examinations before and after preparation on all patients included hemoglobin, hematocrit, sodium, potassium, phosphorous, calcium and serum osmolarity. A questionnaire was used to assess undesirable side effects and patient tolerance to the solution. The quality of preparation was assessed by the endoscopist who was unaware of the solution employed. RESULTS: Statistically significant changes were verified in serum sodium, phosphorous, potassium and calcium between the two groups, but no clinical symptoms were observed. There were no significant differences in the frequency of side effects studied. Six of the eight patients in Group NaP who had taken mannitol for a previous colonoscopy claimed better acceptance of the sodium phosphate solution. The endoscopic-blinded trial reported excellent or good bowel preparation in 85% prepared with sodium phosphate versus 82.5% for mannitol (p=0.37). CONCLUSIONS: Quality of preparation and frequency of side effects was similar in the two solutions. The smaller volume of sodium phosphate necessary for preparation seems to be related to its favorable acceptance. Nevertheless, the retention of sodium and phosphate ions contraindicates the use of sodium phosphate in patients with renal failure, cirrhosis, ascites, and heart failure.